Introductory econometrics a modern approach - Wooldridge, Jeffrey M. 1960- (South Western, Cengage Learning, 2009)
"Econometrics is based upon development of statistical methods for estimating economic relationships, testing economic theories, and evaluating and implementing government and business policy. The most common application of econometrics is the forecasting of such important macroeconomic variables as interest rates, inflation rates, and gross domestic product."